MENU LUHU (Katuk Saorophus Androginus) SEBAGAI KEARIFAN LOKAL DALAM MENINGKATKAN PRODUKSI ASI FREKUENSI DAN DURASI MENYUSUIDI KABUPATEN KEPULAUAN SANGIHE - Semuel Layuk; Daniel Robert; Nonce Nova Legi (POLTEKKES KEMENKES MANADO, 2016)
Background: Feeding behavioris an activityandculturewithin a family, had astrong influenceonwhat, whenandhowpeopleeat. Eating habitsandculturalpatternswillinfluence thetypesoffoodthatshould be consumedboth concerningprocessing and presentationso as tomeetthenutritionalneedsof each family member. Luhuleafis one type ofits kindkatukunknownindetailbutthisis akindkatuktypicalmenuinSangihe Islands Regencyin North Sulawesi.Menuluhuhas longbecomea daily menuby residents ofthe region ofSangihe IslandsRegency, TalaudandSitaro, as a main mealcookedvegetablesare processedintoclearordisantanandspecificallygiven tonursing mothers.Fish, is a kind ofhealthy foodthatislow in saturated fat, high in protein, and is animportant source ofomega 3 fatty acids.The design of the study: The study is a randomized quasy Experimentnon-one-grouppretest and posttest study design will be implemented in some areas of health centers inSangihe Islands Regency in April, 2015. The population in this study were all nursingmothers in the health centers that have Sangihe Islands Regency proportion of nursingmothers and infants with high malnutrition status amounted to 145 people.Univariatedataanalysisusingfrequency distribution tablestoobtaingeneral informationaboutthe characteristics ofthe sampleand therespondents andthe research variables.Bivariateanalysisto determineMenuLuhu(Katuk Saorophusandrogynous) AsLocalWisdomIn Increasingmilk productionFrequencyandDuration ofBreastfeedinginSangiheIslands Regencyusing ChiSquare(X ²) at the95% significance level(α =0.05).Results:MenuLuhumodifiedwith tunagenerallyacceptableasfoodfor nursing mothers.MenuLuhumodified withtunafishcan be used asan alternativemenufor mothers whoarebreast-feedingbecause it canincrease milk productionthrough thefrequencyanddurationof breastfeeding. Tutomodifiedmenuwith tunawhen givenregularly canimprove themother'sweightandcan further improvethe nutritionalstatusof mothersandinfants.MenuLuhumodifiedwith tunais amodified conventionalmenuandcan be receivedbyalocalweaning foodwithoutreducingthe values oflocal wisdom. Menu Luhu modified withtuna is a modified conventional menu and can be received by a local weaning food withoutreducing the values of local wisdom. Menu Luhu modified with tuna into alternative foodsfor breastfeeding mothers that can be patented to the next can be utilized by thecommunity specifically in Sangihe and generally in society as a menu nutritional value.Modifications need to be done again with other food ingredients to increase nutritionalvalue Luhu menu to be more impregnate both micro and macro nutrients that are essentialto increase milk production for breastfeeding mothers.